The use of Arduino software and hardware in a school physical experiment (Educational Dimension, 2020)
The article considers the use of hardware and software Arduino in order to involve students in the study of such subjects as: physics and computer science; provide an opportunity improve and develop their own engineering ideas. The article proves that the use of hardware and software Arduino complex in teaching and research activity is an effective tool for improvement interest in such areas of activity as computer science, engineering, physics. The study found that an integrated approach allows arousing students’ interest in the study of natural sciences and mathematics, solving modern problems engineering and electronics, and developing them creativity. Work on your own projects allows children to show abilities and present their projects in various competitions, in addition motivates young researchers. Developed by students devices can significantly increase accuracy measurements during the experiment, increase the level of theoretical preparation for laboratory work, increase the general interest to perform laboratory work by students for due to the modernization of equipment and form new ones ideas about physical phenomena and processes. The results of students’ research activities can used during the teaching of physics in a specialized school, especially during school experiment.